PELAKSANAAN PERJANJIAN HUTANG PIUTANG ATAS DASAR KEPERCAYAAN (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR:2683 K/Pdt./2016) - Sherry Renata; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2019)
The agreement as described in Article 1313 KUHPer is, an act of mutual adherence to one or more persons. The most common agreement in society is one of the accounts payable receivables. Receivable debt agreements orally are made solely by the words of the parties. The purpose of this writing is to find out how the settlement of the implementation of the loan receivables agreement contains elements of default. This research is a normative legal research. Type of data used is secondary data in the form of primary legal materials, secondary law materials, and non-law material. Technique of collecting data used is study of literature, instrument of research instrument is the decision of Supreme Court of Republic of Indonesia No: 2683 K / Pdt.2016. The verdict on the case of default, ie between Soekotjo as Plaintiff and Melyani as Defendant. Claimed suicide on the ground has made a default on the verbal debt receivable agreement. Melyani denied the amount of the loan sued by Soekotjo because it was considered inappropriate. However, the judge decides that Melyani performs torture. Oral agreements have the power of law, as long as they are proved to have been made by the parties and have been in compliance with the legitimate terms of the agreement set forth in Article 1320 of the Civil Code.